2005
DOI: 10.1007/s10438-005-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of elements and physiologically active compounds in the regulation of synthesis and accumulation of indole alkaloids in Catharanthus roseus L.

Abstract: Effects of various elements (Co, Ni, Zn, W, Mn, Cr, B, Mo, Fe, and V), natural and synthetic auxins, cytokinins, and gibberellin on biosynthesis and accumulation of indole alkaloids was studied at increasing concentrations in the model system of Madagascar periwinkle seedlings ( Catharanthus roseus L.). The main types of concentration dependences for the effect of physiologically active compounds under study were evaluated. A possible mechanism of the influence of Zn and auxin on this process was partly clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Addition of tetramethylammonium bromide induced positive response by increasing ajmalicine content in shake flask and bioreactor [ 9 ]. Effects of a number of elements as Co, Ni, Cr, Cu, B, Mo, Fe, and Vn produced variable response on alkaloid content of 4-6 day old seedlings of Catharanthus [ 10 ]. It is not clear whether metal elicitation studied at cellular level may actually replicate at whole plant level.…”
mentioning
confidence: 99%
“…Addition of tetramethylammonium bromide induced positive response by increasing ajmalicine content in shake flask and bioreactor [ 9 ]. Effects of a number of elements as Co, Ni, Cr, Cu, B, Mo, Fe, and Vn produced variable response on alkaloid content of 4-6 day old seedlings of Catharanthus [ 10 ]. It is not clear whether metal elicitation studied at cellular level may actually replicate at whole plant level.…”
mentioning
confidence: 99%
“…This research group also analysed the changes in the reactive oxygen metabolism of C. roseus in terms of H 2 O 2 content, lipid peroxidation and the free‐radical quenching systems (non‐enzymatic and enzymatic antioxidants) under drought stress and found that ajmalicine was significantly increased over the control [73–75]. Lovkova et al [76] studied the effect of various elements (Co, Ni, Zn, W, Mn, Cr, Cu, B, Mo, Fe and V) and physiologically active compounds, including natural and synthetic auxins, cytokinins and gibberellin, at increasing concentrations, on the synthesis and accumulation of IAs in C. roseus . It was demonstrated that auxin down‐regulated the transcription level of the Str gene in C. roseus cell cultures [77].…”
Section: Effects Of Elicitor On Tia Accumulation In C Roseusmentioning
confidence: 99%
“…often referred to as elicitators, have widely been applied to improve secondary metabolite synthesis in cultivated tissues (Dicosmo and Miswa 1985;Moreno-Valenzuela et al 2003;Zheng and Wu 2004;Junaid et al 2011). Application of various chemicals like osmotic shock, salt stress, elements has been utilized to improve alkaloid yield in cell cultures of C. roseus (Zhao et al 2000(Zhao et al , 2001Lovkova et al 2005;Zahid and Mujib 2012). Some of the enrichment responses of those treatments, although were cell-line specific and often limit their utilization, studies using efficient biotic/abiotic elicitors for improving secondary metabolite synthesis are an important approach in cell cultures (Moreno et al 1995).…”
Section: Introductionmentioning
confidence: 99%